St. Joseph of Quiruvilca rigin and vicissitudes of a miner seat - Espinoza Soriano, Waldermar (2011)
In 1629, mining began in the hills of Quiruvilca, saw the department of La Libertad, but the large vein was discovered and worked since 1634, thanks to the constancy of Fernando de Ahedo and Saravia, founder of the mining seat, who gave it the name of St. Joseph of Quiruvilca. From the start brewing workers were never compelled to mitas. Silver produced good law. Martinez was visited by Compañon, Bishop of the Bourbon era humanist. He had a labor system according to the customs of the XVII to XIX. In the XX came under the control of transnational corporations in addition to silver, other metals extracted. Continues today, during which time has given rise to a large human population living in a urban settement.